(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Introduction: The present study was aimed to know whether the effective communication of dietary recommendations would have added therapeutic benefit in children with functional constipation on laxatives.Material and methods: A total of 106 children of functional constipation, age 1 to18 years who attended general Pediatrics OPD were enrolled. Consecutively enrolled children with odd number were placed in group 1 & rest were placed in group 0. All were advised to take laxative polyethylene glycol (PEG) for 6- 12 months, maintain stool diary & to come for follow up at 10 to15 days,1, 3 & 6 months. Group 0 was attended in usual way in OPD while group 1 was explained the desired changes in diet & toilet schedule in structured format & written handouts were given. Primary outcome was number of stools per week & stool form on BSFS assessed beyond 3 months.Results: Group 1 and 0 were almost same in initial months in terms of cure rates but beyond 3 months the kids in former group were better in terms of softer stools, higher number of stools per week & also subjective improvement reported by many (71 % in group 1 vs 52% in group 0) and fewer relapses (17.8% in former vs 38.9% in later).Conclusion: The effective communication of changes in diet and toilet habits are helpful mainly in long term follow up, associated with higher objective improvement rates &fewer relapses.